Writing for the Instant Messaging and Text Messaging Generation: Using New Literacies to Support Writing Instruction - Sweeny, Sheelah M. (Journal of adolescent & adult literacy, 2010)
Writing, for adolescents who live in an age of digital communication, has taken on new importance and plays a prominent role in the way they socialize, share information, and structure communication. New literacies expand the literacy realm by considering the skills needed to function using media other than the printed page. Internet resources can enhance and expand the writing process by focusing on different writing forms or genres, using video clips of authors to serve as writing mentors, explaining and facilitating the editing and revising processes, and providing publishing opportunities for student writers. This article provides a rationale for the use of new literacies in literacy instruction and explores ways teachers can integrate new literacies into existing writing instruction.